Simultaneous Femoral Osteotomy and Primary Total Knee Arthroplasty in Patient with Severe Extra-articular Deformity : A Case Report - Brahmana, Febrian; Hernugrahanto, Kukuh Dwiputra (The Hip and Knee Journal, 2022)
Correction of an extra-articular deformity of the femur and tibia during total knee arthroplasty (TKA) in advanced knee osteoarthritis (OA) is a technically demanding procedure. The challenge is in the implications of the femoral and tibial realignment osteotomy in both coronal and sagittal planes either as step-by-step or simultaneous procedure. We herein describe an unusual case of knee OA characterized by fixed severe varus knee deformity, tibio-femoral bowing, and lower limb internal rotation. The patient underwent distal femoral osteotomy correction accompanied by TKA to restore mechanical and rotational alignment at the same time. A standard primary posterior stabilized (PS) implant was used. The procedure successfully provided stability, restored alignment and delivered good functional outcome. This case highlights the arthroplasty surgeon’s challenges, especially those who work in limited facilities.